2017 ISHNE‐HRS expert consensus statement on ambulatory ECG and external cardiac monitoring/telemetry. Issue 3 (May 2017) - Steinberg, Jonathan S.; Varma, Niraj; Cygankiewicz, Iwona; Aziz, Peter; Balsam, Paweł; Baranchuk, Adrian; Cantillon, Daniel J.; Dilaveris, Polychronis; Dubner, Sergio J.; El‐Sherif, Nabil; Krol, Jaroslaw; Kurpesa, Malgorzata; et al.
Abstract: Ambulatory ECG (AECG) is very commonly employed in a variety of clinical contexts to detect cardiac arrhythmias and/or arrhythmia patterns which are not readily obtained from the standard ECG. Accurate and timely characterization of arrhythmias is crucial to direct therapies that can have an important impact on diagnosis, prognosis or patient symptom status. The rhythm information derived from the large variety of AECG recording systems can often lead to appropriate and patient‐specific medical and interventional management. The details in this document provide background and framework from which to apply AECG techniques in clinical practice, as well as clinical research.